PENERAPAN VISUALISASI 3D TANAMAN AIR BERBASIS ANDROID PADA MAHASISWA BIOLOGI - Lita Karlitasari; - Ismanto; Agung Prajuhana Putra (Universitas Pakuan, 2017)
This study aims to assist Biology students in studying Plant Taxonomy. 3D visualization of aquatic plants is the result of a transformation that resembles the original image and is dynamic so that it can be viewed in detail from all sides. There are also tools used are Software Photoshop + Blender and Unity 3D, while the required materials are photos of plants that have been taken. The method developed is multimedia application development method used is IMSDD (Interactive Multimedia System Design and Development), where done System Requirement Phase, Design Consideration Phase, Implementation Stage, and Evaluation Phase. Capturing is done with clarity enough brightness, so it will be easy when designing 3D visualization. Plants taken from several Botanical Gardens Region, such as Bogor Botanical Gardens, Ciapus Botanical Garden, Purwodadi Botanical Garden, and Botanical Garden Eka Buana Bali. The picture taken is the whole, stems, flowers, fruit, and leaves both front and rear. Application development is done through the collection of objects, object segmentation, the creation of object textures and the creation of 3D objects. 3D water plants visualization applications can be enlarged and reduced, and rotated well to the right, left, up, and down. Water plants that appear in the application are present in the Indonesian and Latin names, taxon and description. Once the application is complete, it will be transformed to an Android-based platform.Â Keywords : 3D visualization, android, water plants